2016
DOI: 10.5194/acp-16-14925-2016
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the steering principal of tropical cyclone motion in a numerical experiment

Abstract: Abstract. The steering principle of tropical cyclone motion has been applied to tropical cyclone forecasting and research for nearly 100 years. Two fundamental questions remain unanswered. One is why the steering flow plays a dominant role in tropical cyclone motion, and the other is when tropical cyclone motion deviates considerably from the steering. A high-resolution numerical experiment was conducted with the tropical cyclone in a typical large-scale monsoon trough over the western North Pacific. The simul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 46 publications
3
31
0
1
Order By: Relevance
“…In this study a semi-idealized numerical simulation is conducted using version 3.2.1 of the WRF model. Following Wu and Chen (2016), two steps were taken to construct the initial conditions for the numerical experiment. A symmetric vortex was first spun up without the environmental flow on an f plane for 18 h and then the vortex was embedded in the large-scale background of Typhoon Matsa (2005) from 00:00 UTC 5 August to 12:00 UTC 6 August.…”
Section: The Numerical Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study a semi-idealized numerical simulation is conducted using version 3.2.1 of the WRF model. Following Wu and Chen (2016), two steps were taken to construct the initial conditions for the numerical experiment. A symmetric vortex was first spun up without the environmental flow on an f plane for 18 h and then the vortex was embedded in the large-scale background of Typhoon Matsa (2005) from 00:00 UTC 5 August to 12:00 UTC 6 August.…”
Section: The Numerical Experimentsmentioning
confidence: 99%
“…The model is run for 36 h and the 1/9 km resolution and 1/27 km resolution domains are activated at 24 h. In the following analysis, we will focus on the hourly output from 26 to 36 h. The TC center is determined with a variational approach in which it is located until the maximum azimuthal mean tangential wind speed is obtained (Wu et al, 2006).…”
Section: The Numerical Experimentsmentioning
confidence: 99%
“…In this study the numerical simulation is conducted using version 3.2.1 of the WRF model. Following Wu and Chen (2016), two steps were taken to construct the initial conditions for the numerical experiment. A symmetric vortex was first spun up without the environmental flow on an f-plane for 18 hours and then the vortex was embedded in the large-scale background of Typhoon Matsa (2005) from 0000 UTC 5 August to 1200 UTC 6 August.…”
Section: The Numerical Experimentsmentioning
confidence: 99%
“…Recently, Wu and Chen (2016) conducted the potential vorticity tendency (PVT) diagnosis for the sub-kilometer high-resolution simulation of Typhoon Matsa (2005) to address the question why the steering flow is important in TC motion. They found that the conventional deep-layer-mean steering, which is optimally determined over a certain radius from the TC center (defined as the geometric center of the circle on which the azimuthal-mean tangential wind reaches a maximum), plays a dominant role in TC motion because the contributions from other processes are largely canceled out due to the coherent structure of the TC circulation.…”
Section: Revisit To the Concept Of Steering Flowmentioning
confidence: 99%